THE INFLUENCE OF SPATIAL REASONING ABILITY OF STUDENTS OF METHODIST AEK NABARA PRIVATE MIDDLE SCHOOL ON GEOMETRY PROBLEMS THROUGH THE TGT LEARNING MODEL - Santi Nur Cahyani; Amin Harahap; Nurlina Ariani Harahap (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The majority of the mathematics curriculum in junior high school is devoted to geometry. The methods for solving mathematical problems using coordinates, diagrams, and drawings are covered in this topic. This study employs a descriptive quantitative research design. With 70 pupils split up into two classes, the population utilized class VIII at SMP SWASTA METHODIST AEKNABARA. Multiple linear regression tests were performed using the SPSS 24 application as part of the data processing technique. The T count T table with a sig value of 0.000 0.05 indicates that the Teams Games Tournament Learning Model (Tgt) variable was positively and significantly impacted by the T-Test of the Spatial Reasoning Ability variable, Geometry Material. The Teams Games Tournament Learning Model's F Test is concurrently.